Physical therapy in nephrological clinic — is it forgotten, abandoned or useless? - Pyrih, L.A. (KIDNEYS, 2021)
A literature review presented based on the application of various physiotherapeutic modalities in the treatment of kidney diseases, their corrective impact on the pathophysiological disorders in the patient. Based on the questionnaire, the opinion of nephrologists and physiotherapists about the place of physiotherapy in the nephrology clinic is given.